The rising of retail prices during Movement Control Order / Nurul Asyiqin Muthaza, Siti Nurshafiqah Hamzah and Nur Izzah Alya Ruslan - Muthaza, Nurul Asyiqin; Hamzah, Siti Nurshafiqah; Ruslan, Nur Izzah Alya (Faculty of Communication & Media Studies, 2021)
Food is one of life essentials for human and it must have in human life for they to survive. When it comes to life essentials, it is important for human to find ways for those essential keep provided to them. Food becomes energy for human to do chores or working to keep living and surviving the world. However, it is different when the place itself has been infected or having a crisis such as pandemic or war, food becomes number one for them to find. Therefore, there is no such reason for people to abuse the prices of retail of food. The rapid rise in food prices has been a burden on the poor, and more intense when the country is having a big crisis. Reason for retailer to rise their price on retail is burdensome and unnecessary for them to apply. It is because the crisis not only affected on them but other people too who is the buyers. Moreover, when the crisis happened, some of them lose their job and surviving the crisis together as with the retailer. Become survival when they lost their job and have to go through the peak of retail prices just for food. The researchers used qualitative method where is the researchers interview 8 respondents that had experienced the situation itself. The researchers gather the information and socialize with the public to hear their opinion. Being fair and no bias towards any parties, the researchers find out government plays the main role on preventing and investigating the cases due the outbreak of COVID-19. People are confused and concern yet the cases still increasing by time to time and question mark arise when no act have been taken on certain places. Consumers' voice plays major role on keeping government alert regarding the situation and providing solution to solve the issue.